REMAJA PENGUNJUNG CLUB MALAM DI KOTA PEKANBARU - Anugrah, Adhetio; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of this research is: to know the characteristics of teenage nightclub visitors and to know the cause of teenagers to visit the night club. The locationof this research was conducted at MP Club Pekanbaru. research subjects used inthis study were teenagers night club visitors in Pekanbaru City. The selection ofsubjects is done by purposive sampling, then got the subject of research as many as7 teenagers who visited the MP club in the city of Pekanbaru. The method or wayin this study is by way of guided interviews by conducting or holding a directobservation. The type of data used is primary and secondary data. Data analysiswas done by descriptive qualitative method. The result showed 1) in general thecharacteristic of adolescent who likes to visit night club often dressed in sexy,wearing make up and wearing accessories worthy of socialite women, for teenagevisitors of night club, from drinking alcohol, free sex, consumption of drugs andsmoking is not a taboo thing for them to do, and all that is not apart from theiractive social interaction at night and sleep during the day, 2) the factors that causeteenage visitors night club to visit the night club is a social factor where theassociation plays an important role in the formation of personality in the teenagemoments. In general they fall due to the invitation or persuasion of his friends andin added with the curiosity curiosity that exist in themselves.Keywords: teenage, nightclub visitors